Changes in metabolite profiles and antioxidant and hypoglycemic activities of Laminaria japonica after fermentation. (15th March 2022) - Yue, Qiulin; Wang, Zhongjian; Yu, Fupeng; Tang, Xueyang; Su, Le; Zhang, Song; Sun, Xin; Li, Kunlun; Zhao, Chen; Zhao, Lin
Abstract: The seaweed Laminaria japonica is considered as a potentially sustainable marine resource with good nutritional and medicinal value. Saccharomyces cerevisiae and two Lactiplantibacillus strains were added to the starter culture of mixed fermentation of L. japonica . The effects of fermentation on the metabolite profiles and antioxidant and hypoglycemic activities of fermented L. japonica were evaluated. Untargeted metabolomics analysis showed that levels of organic acids, phenolics, vitamins, and unsaturated fatty acids were significantly increased, whereas those of carbohydrates and saturated fatty acids were decreased in fermented samples. Kyoto Encyclopedia of Genes and Genomes analysis indicated that microbial metabolism, amino acid metabolism, and vitamin metabolism were involved in fermentation. In vitro spectrophotometric assays demonstrated that the scavenging activities of ABTS radicals, reducing power, and α-amylase and α-glucosidase inhibitory activities of L. japonica were remarkably enhanced by fermentation. Furthermore, fermented L. japonica showed hypoglycemic effects on insulin-resistant HepG2 cells. Our study provides an effective strategy of step fermentation by S. cerevisiae and Lactiplantibacillus for improving the phytochemical components and bioactivities of seaweeds. Highlights: Seaweed is an edible marine species with good nutritional and medicinal values. Fermentation significantly affects the contents of active compounds. Fermentation strongly influences antioxidant and hypoglycemic activities. Fermentation enhances the quality and health benefits of seaweed.